2014
DOI: 10.1186/s13071-014-0534-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood and bone marrow in selected canine vector-borne diseases

Abstract: BackgroundBone marrow (BM) is a major hematopoietic organ that can harbour a variety of vector-borne pathogens; however, knowledge of BM pathological changes in dogs infected with vector-borne pathogens is limited. Thus, the aim of the present study was to assess the pathological changes in canine BM associated with natural infections by four vector-borne pathogens, as well as to determine the relationships between such changes and abnormalities of the peripheral blood.MethodsCytological disorders and patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 42 publications
0
15
0
3
Order By: Relevance
“…The hematologic profile of leishmaniotic dogs may be complemented by bone marrow cytology, which may be highly diagnostic just by the microscopic identification of amastigotes in macrophages. In addition, the quantitative assessment of the frequency of infected macrophages in a bone marrow smear may allow differentiation between an infected and a sick dog, as the parasite load and the magnitude of cytologic alterations are generally more prominent in dogs with clinical signs, although some histologic studies demonstrated that parasite density can be high despite few clinical signs .…”
Section: Laboratory Abnormalities That May Support or Confirm Leishmamentioning
confidence: 99%
See 1 more Smart Citation
“…The hematologic profile of leishmaniotic dogs may be complemented by bone marrow cytology, which may be highly diagnostic just by the microscopic identification of amastigotes in macrophages. In addition, the quantitative assessment of the frequency of infected macrophages in a bone marrow smear may allow differentiation between an infected and a sick dog, as the parasite load and the magnitude of cytologic alterations are generally more prominent in dogs with clinical signs, although some histologic studies demonstrated that parasite density can be high despite few clinical signs .…”
Section: Laboratory Abnormalities That May Support or Confirm Leishmamentioning
confidence: 99%
“…27 Neutrophilia, due to a systemic inflammatory response, may be present and particularly prominent in cases with ulcerative cutaneous lesions and secondary bacterial infection. 27,28 Conversely, quantitative or qualitative morphologic changes in the other leukocyte populations are less common, although lymphopenia, lymphocytosis, or eosinophilia are occasionally described [28][29][30] Amastigotes are rarely documented in circulating neutrophils, lymphocytes, and monocytes of infected dogs (< 0.5% of cases). 29,31 As the percentage of infected cells is so low, a microscopic search in peripheral blood smears is generally not rewarding.…”
Section: Hematologic Abnormalitiesmentioning
confidence: 99%
“…engulfing of various BM cells by megakaryocytes [40], was also frequently observed in this study. Emperipolesis increases in various disorders, including multiple myeloma, carcinoma, lymphoma [41], platelet disorders [42] and serious hemorrhage [43], however the pathophysiological importance of emperipolesisis is yet to be fully understood and its significance is uncertain [44,45]. Indeed, this event may be linked to the effects of interleukin-6 (IL-6), which alters the process of megakaryocyte maturation, thus altering thrombocytopoiesis [45].…”
Section: (12)mentioning
confidence: 99%
“…Emperipolesis increases in various disorders, including multiple myeloma, carcinoma, lymphoma [41], platelet disorders [42] and serious hemorrhage [43], however the pathophysiological importance of emperipolesisis is yet to be fully understood and its significance is uncertain [44,45]. Indeed, this event may be linked to the effects of interleukin-6 (IL-6), which alters the process of megakaryocyte maturation, thus altering thrombocytopoiesis [45]. To our knowledge, prior to the present study, emperipolesis had only been described in dogs infected by L. infantum [8] and A. platys [39]; we describe, for the first time, emperipolesis in dogs infected or co-infected by H. canis.…”
Section: (12)mentioning
confidence: 99%
“…Another study found that Anaplasma platys, a tick‐transmitted, obligate intra‐platelet rickettsial pathogen, can infect megakaryocytes and promegakaryocytes in dogs . Anemia, thrombocytopenia, and pancytopenia are well‐recognized hematopoietic or immune‐mediated abnormalities in dogs infected with Ehrlichia canis . Among other hematological abnormalities, dysgranulopoiesis and dysmegakaryocytopoiesis were the most frequently observed bone marrow abnormalities in dogs infected with Anaplasma platys, Leishmania infantum, Babesia vogeli , and Hepatozoon canis .…”
Section: Discussionmentioning
confidence: 99%